The Application of Video Games in Education - Diego Rodríguez-Ponga (Ignatianum University Press, 2021)
There is a lack of motivation in high schools that is difficult to ignore. This is even worse in the case of history courses, which are perceived by students as "useless." Many would cite video games and mobile phones as some of the technological changes that explain how teenagers are less interested in such subjects. However, there is an enormous educational potential in video games that should not be ignored. This work is an explanation of how history can be translated not only through audio-visual language, but also in the form of a new type of word: ludic language. Moreover, an educational activity is proposed in order to find a solution to this lack of motivation. For this activity, the Early Modern period simulator Europa Universalis IV has been chosen as the video game to be implemented in a history class for 14-year-olds.